2021
DOI: 10.3390/md19050274
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Nostoxanthin Production by Sphingomonas sp. SG73 Isolated from Deep Sea Sediment

Abstract: Carotenoids are used commercially for dietary supplements, cosmetics, and pharmaceuticals because of their antioxidant activity. In this study, colored microorganisms were isolated from deep sea sediment that had been collected from Suruga Bay, Shizuoka, Japan. One strain was found to be a pure yellow carotenoid producer, and the strain was identified as Sphingomonas sp. (Proteobacteria) by 16S rRNA gene sequence analysis; members of this genus are commonly isolated from air, the human body, and marine environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Achromobacter and Sphingomonas of Proteobacteria, uncultured_Bacteroidetes and Ambiguous_Actinobacteria were the most enriched in HFSs; while Nitrosopumilus and three uncultured genera of Thaumarchaeota and the uncultured Urania-1B-19 group of Planctomycetes were the most enriched in NHFSs (LDA > 4.0, P < 0.05, Supplementary Figure S5). Members of the genera Achromobacter and Sphingomonas have previously been found in deep-sea sediments (Zhang et al, 2014;Yang et al, 2020b;Kikukawa et al, 2021), and this is the first study to demonstrate that they are enriched in HFSs. In the previous studies of microbial diversity in deep-sea hydrothermal vents, Nitrosopumilus was found to adapt to inactive vents or cooler ecological niches of the vents (Zhang et al, 2016;Cerqueira et al, 2017).…”
Section: Diversity and Distribution Of Prokaryotic Communitiesmentioning
confidence: 60%
“…Achromobacter and Sphingomonas of Proteobacteria, uncultured_Bacteroidetes and Ambiguous_Actinobacteria were the most enriched in HFSs; while Nitrosopumilus and three uncultured genera of Thaumarchaeota and the uncultured Urania-1B-19 group of Planctomycetes were the most enriched in NHFSs (LDA > 4.0, P < 0.05, Supplementary Figure S5). Members of the genera Achromobacter and Sphingomonas have previously been found in deep-sea sediments (Zhang et al, 2014;Yang et al, 2020b;Kikukawa et al, 2021), and this is the first study to demonstrate that they are enriched in HFSs. In the previous studies of microbial diversity in deep-sea hydrothermal vents, Nitrosopumilus was found to adapt to inactive vents or cooler ecological niches of the vents (Zhang et al, 2016;Cerqueira et al, 2017).…”
Section: Diversity and Distribution Of Prokaryotic Communitiesmentioning
confidence: 60%
“…MicrOTOF-QII mass spectrometry (Bruker, Bremen, Germany) and AB SCIEX (X500R, Framingham, MA, USA) mass spectrometry was used for pigment identification. The electrospray ionization-time of flight-mass spectrum (ESI-TOF-MS) spectra were obtained by scanning from m/z 50 to 1200 with a dry heater at 180 °C, capillary voltage of 4500 V, and collision cell RF of 150.0 Vpp [ 26 ]. To acquire the specific structure of the pigment produced by strain GH-1, high-resolution mass spectrometry (HRMS) was used to analyze the ion fragments of the pigment [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To recover the remaining carotenoids from each protein, the precipitated protein was resuspended in 0.2 mL of acetone, vortexed and centrifuged (16,000× g , 5 min, 4 °C), and then the resulting second supernatant was mixed with the first supernatant (total 0.6 mL). The carotenoid concentrations were determined as described previously [ 24 , 25 ] using a high-performance liquid chromatography system (Shimadzu, Kyoto, Japan) equipped with a COSMOSIL Cholester Packed Column (4.6 i.d. × 250 mm, Nacalai Tesque, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%